Photo analyses of a fully submerged static vehicles on different water velocity / Mohamad Adam Muqri Abdul - Abdul, Mohamad Adam Muqri (2022)
This project demonstrates the hydrodynamic state of a stationary vehicle submerged in a moving water channel. Recent study uses the Wind Tunnel machine in order to find the lift and drag forces. However, a Circulating Water Channel can also be used. The concepts are quite similar but the CWC machine uses the concept of fluid dynamics. The objectives of this study are to determine the flow pattern of fully submerged model of sports car, ambulance, a jeep in different water velocity that is fully submerged underwater and to analyse the effect of lift and drag force on different vehicle models on flow pattern that formed. The experiments will be carried out using the Circulating Water Channel machine (CWC) under four Submerged Ratio (SR) conditions, such as the height of the pitot tube from the bottom, suggesting that the water pressure and flow velocity varied. A Digital Single-Lens Reflect (DSLR) Camera will be used to capture of flow pattern of water during around the vehicle models during the experiment. Then, in order to compare the three objects, the difference in pressure and flow results will be observed. The influence of flow pattern on three vehicles models are investigated. Then the drag and lift force will be calculated it is expected that a better aerodynamic shape will result to a better lift and drag forces.